2013
DOI: 10.1103/physrevlett.110.104103
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Symmetry Breaking Induced by Third-Order Dispersion in Optical Fiber Cavities

Abstract: We study analytically, numerically, and experimentally the nonlinear symmetry breaking induced by broken reflection symmetry in an optical fiber system. In particular, we investigate the modulation instability regime and reveal the key role of the third-order dispersion on the asymmetry in the spectrum of the dissipative structures. Our theory explains early observations, and the predictions are in excellent agreement with our experimental findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 34 publications
3
38
0
Order By: Relevance
“…In particular, third-order dispersion (TOD) generates the emission of dispersive waves that can lead to the suppression of dynamical regimes such as oscillations and chaos [26,27]. As TOD also breaks reversibility, solitons move with a constant velocity [26][27][28][29][30]. While recent work has numerically shown that TOD induces similar dispersive waves in dark solitons in both normal and anomalous dispersion regions [31], a complete understanding of the influence of TOD on the dynamics and bifurcation structure of dark pulse Kerr frequency combs is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, third-order dispersion (TOD) generates the emission of dispersive waves that can lead to the suppression of dynamical regimes such as oscillations and chaos [26,27]. As TOD also breaks reversibility, solitons move with a constant velocity [26][27][28][29][30]. While recent work has numerically shown that TOD induces similar dispersive waves in dark solitons in both normal and anomalous dispersion regions [31], a complete understanding of the influence of TOD on the dynamics and bifurcation structure of dark pulse Kerr frequency combs is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This higher-order term strongly modifies the dynamics of nonlinear systems by making them convectively unstable [21]. In optical fibers, it leads to the nonlinear symmetry breaking of parametric processes [22][23][24]28], to the generation of Cherenkov radiations (CRs) by solitons [29], which are one of the key elements of supercontinuum generation [30,31], and, in extreme cases, to turbulent dynamics [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…If the dispersion cannot be considered to be a constant over the spectrum, the TOD term must be taken into account [21][22][23][24][25][26][27][28]. This higher-order term strongly modifies the dynamics of nonlinear systems by making them convectively unstable [21].…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in previous works [52,53], the passive cavity does not operate as a resonant 'phase-sensitive interferometer' [54,55,[83][84][85][86][87][88], and the temporal modes of the cavity do not play any key role in the dynamics of the incoherent wave. The wave circulating in the cavity and the pump wave are thus mutually incoherent with each others, and the boundary conditions are not sensitive to the random relative phase among them:…”
Section: Modelmentioning
confidence: 98%